OP0248 Responder Analysis of the Effects of Abaloparatide (Parathyroid Hormone Related Peptide) and Teriparatide on Bone Mineral Density in Postmenopausal Women with Osteoporosis: Results of the Active Trial. (9th June 2015) - Miller, P.D.; Hattersley, G.; Lau, E.; Alexandersen, P.; Hala, T.; Mustatea, S.; Nedergaard, B.S.; Krogsaa, A.; Slessinger, J.; Zerbini, C.; Valter, I.; Visockiene, Z.; et al.
Abstract : Background: Early gains in total hip BMD are desirable to improve hip strength early in the treatment of osteoporosis. Objectives: To determine if women treated with 18-months of abaloparatide (ABL) were more likely to increase BMD than those treated with either TPTD or placebo (PBO), we performed a responder analysis comparing the percentage of subjects experiencing BMD gains of >3% at all three anatomic sites (total hip (TH), femoral neck (FN), lumbar spine (LS)). Methods: In an 18 month phase 3 study of postmenopausal women aged 50-85 with a T-score ≤-2.5 at the spine or hip with either a prior vertebral or non-vertebral fracture, subjects were randomized to receive the PTHrP analog, ABL (80-μg SC daily), TPTD (20-μg SC daily), or placebo. All subjects were also treated with calcium and vitamin D supplementation per local practice. Treatment comparisons were performed using a 2-sided Chi-square test. Results: 18-months of treatment with ABL (N=824) resulted in significantly greater increases in BMD relative to placebo (N=821) at 6, 12 and 18 months at TH, FN and LS. There were also significantly greater increases in BMD with ABL relative to TPTD (N=818) at TH and FN at 6, 12 and 18 months and at LS at 6 and 12 months. Overall, a significantly higher percentage of patients experienced >3% BMD gain in the ABL group (54%) compared to the PBO group (3.38%, p<0.0001) and the TPTD group (39.7%, p<0.0001) at TH, FN and LS combined. The percentage of subjects with increases in BMD with TPTD was also significantly higher relative to PBO, p<0.0001. Conclusions: In postmenopausal women with osteoporosis, more subjects treated with ABL experienced BMD increases at all 3 sites compared to those treated with TPTD or PBO. Disclosure of Interest: P. Miller Grant/research support from: Radius Health, G. Hattersley Employee of: Radius Health, E. Lau Grant/research support from: Radius Health, P. Alexandersen Grant/research support from: Radius Health, T. Hala Grant/research support from: Radius Health, S. Mustatea Grant/research support from: Radius Health, B. Nedergaard Grant/research support from: Radius Health, A. Krogsaa Grant/research support from: Radius Health, J. Slessinger Grant/research support from: Radius Health, C. Zerbini Grant/research support from: Radius Health, I. Valter Grant/research support from: Radius Health, Z. Visockiene Grant/research support from: Radius Health, B. Jendrych Grant/research support from: Radius Health, C. Kulak Grant/research support from: Radius Health, F. Marquez Grant/research support from: Radius Health, A. Harris Employee of: Radius Health, G. Williams Employee of: Radius Health, M.-Y. Hu Employee of: Radius Health, D. Black Consultant for: Radius Health, B. Riis Consultant for: Radius Health, L. Russo Grant/research support from: Radius Health, C. Christiansen Consultant for: Radius Health